Morphophysiological and transcriptomic analyses during the development of microspores and megaspores in Orobanche coerulescens - Cui, Kelin; Liu, Jingyi; Xie, Yuanyuan; Xiao, Yaqin; Tian, Yuxin; Jiang, Lijuan; Niu, Yandong (Frontiers in Plant Science, 2025)
IntroductionOrobanche coerulescens is a parasitic plant considered as a malignant weed due to its harmful effects on crops. However, its richness in high-value secondary metabolites makes it a significant medicinal resource. The development of microspores and megaspores is essential for sexual reproduction in plants but research on this aspect of O. coerulescens is lacking.MethodsThis study aimed to systematically observe the developmental processes of microspores and megaspores in O. coerulescens using microscopic techniques. We measured the levels of soluble sugar, starch, and phytohormones during different developmental stages. We also investigated the key regulatory genes in the metabolic pathways of phytohormones that are closely related to the development of microspores and megaspores using transcriptome sequencing technology.Results and discussionThe findings revealed that the flower development process of O. coerulescens could be categorized into six stages. Mature pollen was tricellular, with downy ornamentation and pores on the outer wall. The embryo sac was the monosporangiate polygonum type, and the ovule was inverted. The megaspores developed and matured about 15 days later than the microspores. The soluble sugar level of the flower buds decreased initially and then increased during development, whereas the starch level showed an opposite trend. The levels of strigolactone, auxin, and gibberellins gradually increased throughout the development process. The key genes regulating phytohormone synthesis during the development of microspores and megaspores were identified as ALDHs (Aldehyde Dehydrogenases). In contrast, the key genes regulating phytohormone signaling included TIR1 (Transport Inhibitor Response 1) and IAA3 (Indole-3-acetic Acid Inducible 3), and the key TF was ARF5 (AUXIN RESPONSE FACTOR 5). The findings of this study enhanced the understanding of O. coerulescens biology, providing theoretical references for regulating its reproduction, implementing biological control measures, maintaining its population, and optimizing resource utilization.